2012
DOI: 10.1097/ta.0b013e3182606301
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation with washed aged packed red blood cell units decreases the proinflammatory response in mice after hemorrhage

Abstract: BACKGROUND Resuscitation with blood products instead of crystalloid in the treatment of hemorrhagic shock has been associated with improved outcomes in trauma patients requiring massive transfusions and transfusion of fresh products results in reduced morbidity and mortality compared with aged blood. Processes to eliminate harmful components of aged blood are under investigation. We hypothesized that washing blood would reduce levels of proinflammatory mediators in stored units, and resuscitation with washed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 23 publications
(26 reference statements)
1
37
0
Order By: Relevance
“…Noninfectious murine models are contradictory; some studies report that washed older blood induces a significantly lower inflammatory cytokine response, whereas others show that washing had no effect on this response. 35,37 Iron has also been shown to inhibit cellular immune function, mainly through monocyte effector pathways, 38,39 and to impair neutrophil function, 40 affecting the host´s response to bacteria and possibly worsening the infection and outcome in our study. In addition, iron participates in the formation of toxic reactive oxygen species, which contribute directly to the pathogenesis of endothelial Figure 6.…”
Section: Discussionmentioning
confidence: 76%
“…Noninfectious murine models are contradictory; some studies report that washed older blood induces a significantly lower inflammatory cytokine response, whereas others show that washing had no effect on this response. 35,37 Iron has also been shown to inhibit cellular immune function, mainly through monocyte effector pathways, 38,39 and to impair neutrophil function, 40 affecting the host´s response to bacteria and possibly worsening the infection and outcome in our study. In addition, iron participates in the formation of toxic reactive oxygen species, which contribute directly to the pathogenesis of endothelial Figure 6.…”
Section: Discussionmentioning
confidence: 76%
“…While recent studies have shown that storage of murine RBC for ~2 weeks is equivalent to human RBC storage for 42 days based on RBC stability and recovery post transfusion[10, 27, 32], the effects on NO-dioxygenation and nitrite oxidation kinetics are not known. C57BL/6 RBC were leukoreduced using either microcellulose Sephadex G25-columns or by neonatal Sepacell filters (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data provide mechanistic insights into how transfusions with stored RBC inhibit endogenous NO signaling in the vasculature and suggest that NO-repletion strategies, or approaches that remove components in stored RBC that inhibit NO signaling could be beneficial. In the latter context, RBC washing immediately before transfusion to remove microparticles, cell-free hemoglobin, and iron, prevented many of the negative effects of storage in a canine model of transfusion and infectious lung injury[26] and attenuated cytokine levels in a mouse model of trauma-hemorrhage[27] . In the current study, we show similar protective effects of washing towards acute lung injury and lethality in a murine model of trauma-hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors may contribute to its increased mortality when used in the hemorrhaging trauma patient [82]. Pre-storage procedures such as leukoreduction and washing have been shown to decrease the inflammatory response, making the transfusion of aged pRBCs a viable option for these patients [77,83]. Through the various mechanisms described above, as well as its proven role in T cell suppression [84], the number of units of pRBCs transfused has been shown to be an independent risk factor for mortality in this population [77,85].…”
Section: Blood Productsmentioning
confidence: 99%